Analysis of apoptosis via reticular pathway (caspase 12) in L-arginine induced cell death in rats’ hepatocytes - Pedrycz, Agnieszka; Siermontowski, Piotr; Baran, Piotr; Orłowski, Marcin (Current Problems of Psychiatry, 2012)
The aim of present study was assessment of reticular pathway of nitric oxide induced programmed cell death. In intrinsic pathway if apoptosis the mitochondria or endoplasmic reticulum are involved. This is the result of cellular stress and destruction endoplasmic membranes in the cell. In experiment we used rats divided into two groups. Animals from experimental group received L-arginine -precursor of nitric oxide. Specimens taken from liver of decapitated rats was prepared to immunohistochemical method detected caspase 12. Caspase 12 is the enzyme in endoplasmic reticulum. We used standard three step method. In the slides of the liver of rats from experi-mental and control group we didn’t detect overexpression of caspase 12.